Energy-Efficient Harvested-Aware Clustering and Cooperative Routing Protocol for WBAN (E-HARP) - Zahid Ullah; Imran Ahmed; Fakhri Alam Khan; Muhammad Asif; Muhammad Nawaz; Tamleek Ali; Muhammad Khalid; Fahim Niaz (IEEE Access)
Wireless body area network (WBAN) is an interconnection of small bio-sensor nodes (BSNs) that are deployed in/on different parts of human body. It is used to sense health-related data, such as rate of heart beat, blood pressure, blood glucose level, electro-cardiogram (ECG), and electro-myography (EMG), of human body and pass these readings to real-time health monitoring systems. WBANs are the important research area and are used in different applications, such as medical field, sports, entertainment, and social welfare. BSNs or simply called sensor nodes (SNs) are the main backbone of WBANs. SNs normally have very limited resources due to its smaller size. Therefore, minimum consumption of energy is an essential design requirement of the WBAN schemes. In the proposed work, Energy-efficient Harvested-Aware clustering and cooperative Routing Protocol for WBAN (E-HARP) are presented. The presented protocol mainly proposes a novel multi-attribute-based technique for dynamic cluster head (CH) selection and cooperative routing. In the first phase of this two-phased technique, optimum CH is selected among the cluster members, based on calculated cost factor (CF). The parameters used for calculation of CF are residual energy of SN, required transmission power, communication link signal-to-noise ratio (SNR), and total network energy loss. In order to distribute load on one CH, E-HARP selects new CH in each data transmission round. In the second phase of E-HARP, data are routed with cooperative effort of the SN, which saves the node energy by prohibiting the transmission of redundant data packets. To evaluate the performance of the proposed technique, comprehensive experimentations using the NS-2 simulation tool has been conducted. The results are compared with some latest techniques, named EH-RCB, ELR-W, Co-LAEEBA, and EECBSR. The acquired results show a significant enhancement of E-HARP in terms of network stability, network life time, throughput, end-to-end delay, and packet delivery ratio.